L’eau, source de savoirs : analyse de situations d’expertise dans des bassins versants agricoles - Sandrine Petit; Fabienne Barataud (VertigO, 2015)
Preserving water quality implies to call upon and share different knowledge. From the claim that actors on the field associate a diversity of knowledge, in this paper we analyse cases of water protection in two catchment areas, considered as “situations of expertise”. Our results lie in four key points describing the relation between knowledge and management decisions and shedding light on the difficulties of finding situated and locally adapted solutions : (i) cognitive activity or knowledge production are not seen as a social and epistemic practice implying knowledge exchange, sharing and debate. Controversial situations are avoided to act fast ; (ii) knowledge coming from farmers and lay people experience is little used as a relevant causality model compared with other knowledge approaches (experimentation, computer modeling, GIS) ; (iii) the social knowledge about the situation is not included in the diagnosis even if social relations impact the actions implementation ; (iv) the management actions result from a reduction of possibilities funnelled through two filters : the first one, diagnosis characteristics (the expertise constitutes the action) which tend to promote an adaptation of practices rather than a change of agricultural production model ; the second filter is that of legitimacy (legitimate expertise), taken decisions are those admitted by the different social groups.